THE IMPACT OF MACROECONOMIC UNCERTAINTY AND OIL PRICES ON FOOD PRICES: EMPIRICAL EVIDENCE FROM SERBIA - Mladenović, Zorica; Milošević, Emilija (Economics of Agriculture, 2025)
The purpose of the paper is to investigate the impact of crude oil prices and domestic macroeconomic uncertainty on food prices in Serbia over the period 2007-2022. The methodological framework is based on cointegration analysis and the structural vector autoregressive model. The empirical results indicate significant and positive long term effects of uncertainty and oil prices on food prices. Over a one-year horizon, about one-third of the fluctuations in food prices can be attributed to the variability of shocks in uncertainty and oil prices, while their relative influence is slightly more than half after two years. The impact of uncertainty on food price variability peaks within six months, after which its influence diminishes. In contrast, the impact of oil prices gradually increases and becomes the dominant factor in the variability of food prices after a year and a half.